Attributable mortality and excess length of stay associated with third-generation cephalosporin-resistant Enterobacterales bloodstream infections: a prospective cohort study in Suva, Fiji. (September 2022) - Loftus, Michael J.; Young-Sharma, Tracey E.M.W.; Lee, Sue J.; Wati, Shitanjni; Badoordeen, Gnei Z.; Blakeway, Luke V.; Byers, Sally M.H.; Cheng, Allen C.; Cooper, Ben S.; Cottingham, Hugh; Jenney, Adam W.J.; Hawkey, Jane; et al.
Highlights: Pacific island countries have contributed few data to global AMR burden estimates. We assessed the impact of third-generation cephalosporin resistance (3GC-R) in Fiji. 3GC-R was common but mortality was high regardless of the resistance profile. We found minimal impact by 3GC-R on the adjusted hazard of in-hospital mortality. 3GC-R infections were associated with an increased length of hospital stay. ABSTRACT: Objectives: There are scant primary clinical data on antimicrobial resistance (AMR) burden from low- and middle-income countries (LMICs). We adapted recent World Health Organization methodology to measure the effect of third-generation cephalosporin resistance (3GC-R) on mortality and excess length of hospital stay in Fiji. Methods: We conducted a prospective cohort study of inpatients with Enterobacterales bloodstream infections (BSIs) at Colonial War Memorial Hospital, Suva. We used cause-specific Cox proportional hazards models to estimate the effect of 3GC-R on the daily risk (hazard) of in-hospital mortality and being discharged alive (competing risks), and we used multistate modelling to estimate the excess length of hospital stay. Results: From July 2020 to February 2021 we identified 162 consecutive Enterobacterales BSIs; 3GC-R was present in 66 (40.7%). Crude mortality for patients with 3GC-susceptible and 3GC-R BSIs was 16.7% (16/96) and 30.3% (20/66), respectively. 3GC-R was not associated with the in-hospital mortality hazard rate (adjusted hazard ratio [aHR] 1.13, 95% confidence interval [CI] 0.51–2.53) or being discharged alive (aHR 0.99, 95% CI 0.65–1.50), whereas Charlson comorbidity index score (aHR 1.62, 95% CI 1.36–1.93) and Pitt bacteraemia score (aHR 3.57, 95% CI 1.31–9.71) were both associated with an increased hazard rate of in-hospital mortality. 3GC-R was associated with an increased length of stay of 2.6 days (95% CI 2.5–2.8). 3GC-R was more common among hospital-associated infections, but genomics did not identify clonal transmission. Conclusion: Patients with Enterobacterales BSIs in Fiji had high mortality. There were high rates of 3GC-R, which was associated with increased hospital length of stay but not with in-hospital mortality.